Molecular detection of Porcine cytomegalovirus (PCMV) in wild boars from Northeastern Patagonia, Argentina - de Maio, Ana de Las Mercedes (2021)
Porcine cytomegalovirus (PCMV) is a recognized pathogen of domestic swine that is widely distributed around the world. PCMV is the etiological agent of inclusion body rhinitis and has also been associated with other diseases that cause substantial losses in swine production. Wild boar populations can act as reservoirs of numerous infectious agents that affect pig livestock, including PCMV. The aim of this work was to assess the circulation of this virus in free-living wild boars that inhabit Northeastern Patagonia (Buenos Aires and Río Negro Provinces), Argentina. Nested-PCR assays were conducted to evaluate the presence of PCMV in samples of tonsil tissue collected from 62 wild boar individuals. It was found that the overall rate of infection was about 56%, with significant higher values (almost 90%) in the age group corresponding to piglets (animals less than 6 months old). In addition, a seasonal variation was observed in the PCMV detection rate, with an increase during the transition from summer to autumn. In conclusion, this study confirmed that wild boars are major carriers and dispersal agents of PCMV in Northeastern Patagonia, which raises the necessity to evaluate the extent to which this virus affects local livestock production.